Planning Modification of Steel Arch Bridge on Cimanuk Bridge Tomo District Sumedang Regency Cirebon-Bandung Highway - Roesdiana, Tira; Kholiah, Mif’fetin (Journal of Green Science and Technology, 2025)
One of the businesses that supports transportation is the construction of Bridge infrastructure. In improving and supporting transportation facilities, the condition of the bridge must be in good condition. The Cimanuk Bridge which originally used the Steel Box Girder & Steel I Girder structure with a pillar in the middle of the span, the structure will be modified into An Arch Steel Bridge without pillars. Cimanuk Bridge is ± 100 m long, including a long-span bridge so that it can use An Arch Steel Bridge Structure. [1] SNI 1726:2019 about Seismic analysis for design It uses the equivalent static. Analysis method based on SNI 1729: 2020 about Specification for structural steel building. And SNI 1725:2016 about Loading for bridges. The methode of structural analysis performed using SAP2000 version 22 software. The structural calculation process includes the determination of the structural system, load analysis, structural modeling, internal force analysis, reinforcement calculation, and examination of structural element requirements. The result show main structure profile using Double WF 700x550x40x45, Longitudinal Girder WF 500x200x10x16, Transverse Girder WF 1200x500x20x28, Tie Beam BOX 1000x1000x50, Wind Bracing using Square/Box. Keyword: Arch Steel Bridge; Cimanuk Bridge; Steel Structure; SNI 1729:2019; SNI 1725:2016